Seasonal and epidemiological profile of chickenpox cases in Kazakhstan - Sauran Yerdessov; Anara Abbay; Zhalaliddin Makhammajanov; Arnur Gusmanov; Yesbolat Sakko; Gulnur Zhakhina; Kamilla Mussina; Dmitriy Syssoyev; Aidar Alimbayev; Abduzhappar Gaipov (National Scientific Medical Center, 2023)
Background: According to the National infectious disease monitoring report, there is a fluctuating pattern of incidence of chickenpox in the country, but there are no studies reporting the epidemiological situation in Kazakhstan. There is a discernable association of varicella epidemiology with climate, particularly temperature dependency. We aimed to analyze the incidence and seasonality of chickenpox in the absence of universal varicella vaccination in Kazakhstan. Material and methods: A retrospective analysis of the long-term dynamics of chickenpox was carried out, and data he state report "Sanitary and epidemiological situation in the Republic of Kazakhstan for 2020" and data from the Unified Payment System (UPS) from 2014 to 2020 were used. of registered patients between 2010 and 2020 were retrieved from the National infectious disease monitoring report and the Unified Payment System (UPS) database from 2014 to 2020, which is part of the Unified National Electronic Health System (UNEHS). Results: The highest incidence rate for the studied period was registered in 2014 - 363.96 and the lowest was in 2020 - 95.8 per 100,000 population. Overall, 17,520 cases of chickenpox were recorded with an incidence rate of 95.8 per 100,000 population in the country in 2020 (against 41,841 cases, with an indicator of 228.9 in 2019). The highest proportion of cases is observed among children from 4 to 6 years old (29%), children from 1 to 3 years old  (24%)  and  from 7 to 9 years old (15%) . Similar to previous years, there was an autumn-winter spreadingdistribution of morbidity, with the highest registration of morbidity in January. Conclusion: The findings of this study can aid in the prediction of epidemics and the preparation for the impact of climate change on the disease mentioned in epidemiology by implementing preventive puBased on our study, the highest incidence rate of chickenpox in Kazakhstan was registered in 2014 (363.96 per 100,000 population) and morbidity was distributed in the autumn-winter season. These findings might aid in forecasting future outbreaks of infection based on the influence of climate change on chickenpox, and help in making a decision about the implementation of varicella preventive and control initiatives in the country.